The role of rodents in the ecology of Ixodes ricinus and associated pathogens in Central and Eastern Europe - Mihalca, Andrei D.; Sándor, Attila D. (Frontiers in Cellular and Infection Microbiology, 2013)
Rodents comprise more species than any other mammal order. Most rodents are considered keystone species in their ecological communities, hence the survival of many other species in the ecosystem depend on them. From medical point of view, this is particularly important for rodent-dependent pathogens. In the particular case of tick-borne diseases, rodents are important as hosts for vector ticks and as reservoir hosts (Lyme borreliosis, human granulocytic anaplasmosis, Crimean-Congo hemorrhagic fever, Tick-borne relapsing fevers, tick-borne rickettsioses, babesiosis). Community and population ecology of rodents was shown to be correlated with disease ecology in the case of many tick-borne diseases. In Eastern Europe, several adult hard-tick species use rodents as their principal hosts: Ixodes apronophorus, I. crenulatus, I. laguri, I. redikorzevi, I. trianguliceps. However, the majority of ticks feeding on rodents are immature stages of ticks which as adults are parasitic on larger mammals. Larvae and nymphs of I. ricinus, the most abundant and medically important tick from Europe, are commonly found on rodents. This is particularly important, as many rodents are synanthropic and, together with other micromammals and birds are often the only available natural hosts for ticks in urban environments. This work reviews the correlated ecology of rodents and Ixodes ricinus.